Emergency repair strategy of distribution network under wind disaster based on multidimensional importance evaluation - Wenjie Wu; Hui Hou; Xixiu Wu; Ruizeng Wei; Huan He; Ying Shi (Energy Reports, 2023)
In order to enhance the power supply reliability of distribution network under wind disasters and provide assistance for distribution network operators to formulate post disaster repair strategies, this paper proposes an optimization method for key nodes and lines evaluation and distribution network repair strategy under wind disaster. Firstly, based on the complex network theory, we considered the status of nodes and lines in the topology and working state. The multi-dimensional evaluation indexes are proposed including improved node degree, node cohesion degree, node intermediate number, weighted line intermediate number, line transfer power flow entropy and line failure rate, etc. Then, the entropy weight method is used to objectively weight the six indicators, and TOPSIS algorithm is used to rank the comprehensive importance of nodes and lines in the distribution network. On this basis, the dynamic programming theory is used to optimize the emergency repair strategy of the fault distribution network after the wind disaster. And the problem of restoring as many key nodes and lines as possible in a short time is proposed. Finally, the method is applied to the IEEE 39 bus system network to verify the feasibility.